STUDI PENILAIAN SATUAN PENDIDIKAN AMAN BENCANA (SPAB) SEKOLAH BERBASIS KEAGAMAAN DI KABUPATEN CILACAP - Ike Fitri Samsiyah; Imam Mahdi; Albertus Erico Jerry Krisna Nugroho; Pipit Wijayanti (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
EVALUATION STUDY OF DISASTER SAFE EDUCATION UNIT (SPAB) RELIGIOUS BASED SCHOOLS IN CILACAP REGENCY This study aims to evaluate the implementation of the Disaster Safe Education Unit (SPAB) program in religious boarding schools in Cilacap Regency, which has a high level of disaster risk. The study uses a mixed method approach by combining quantitative data through structured questionnaires and qualitative data through in-depth interviews and direct observation of school conditions. Data collection techniques were carried out by distributing questionnaires to teachers and educational staff, interviewing school management, and observing disaster preparedness facilities and activities in the field. Two schools under the Ya BAKII Kesugihan Foundation, namely MA MINAT Kesugihan and SMA Ya BAKII Kesugihan, were the subjects of this study. The assessment was based on the three main pillars of SPAB: safe learning facilities, disaster management and educational continuity, and disaster risk reduction and resilience education. The results of the study showed that both schools were in the “almost ready” category. MA MINAT scored 61.54% (Pillar 1), 54.74% (Pillar 2), and 68.42% (Pillar 3) with an average of 61.57%, while SMA Ya BAKII recorded 66.67% (Pillar 1), 50.36% (Pillar 2), and 26.32% (Pillar 3) with an average of 47.78%. The main challenge was found in Pillar 3 related to the sustainability of disaster education. This study emphasizes the importance of strengthening school policies, teacher training, and cross-party collaboration to strengthen a disaster-aware culture in boarding schools.